2006
DOI: 10.1007/11744047_44
|View full text |Cite
|
Sign up to set email alerts
|

A Boundary-Fragment-Model for Object Detection

Abstract: Abstract. The objective of this work is the detection of object classes, such as airplanes or horses. Instead of using a model based on salient image fragments, we show that object class detection is also possible using only the object's boundary. To this end, we develop a novel learning technique to extract class-discriminative boundary fragments. In addition to their shape, these "codebook" entries also determine the object's centroid (in the manner of Leibe et al. [19]). Boosting is used to select discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
232
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(233 citation statements)
references
References 26 publications
0
232
0
1
Order By: Relevance
“…For instance, in [94] multiple boundary fragments to weak classifiers were composed and formed a strong "boundary-fragment-model" detector using boosting. They ensured the feasibility of the feature selection process by limiting the number of boundary fragments to 2-3 for each weak classifier.…”
Section: Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in [94] multiple boundary fragments to weak classifiers were composed and formed a strong "boundary-fragment-model" detector using boosting. They ensured the feasibility of the feature selection process by limiting the number of boundary fragments to 2-3 for each weak classifier.…”
Section: Feature Extractionmentioning
confidence: 99%
“…A number of follow-up works showed that there is indeed information in the results from the previous nodes, and it is best to reuse them [80,19] etc. Spectral histogram [86] Spatial histogram (LBP-based) [87] HoG and LBP [88] Region covariance [89] SURF [102,103] Composite Joint Haar-like features [62] features Sparse feature set [90] LGB, BHOG [22] Integral Channel Features on HoG and LUV (Headhunter) [26] HoG, HSV, RGB, LUV, Grayscale, Gradient Magnitude [105] Shape features Boundary/contour fragments [94,95] Edgelet [96] Shapelet [97] instead of starting from scratch at each new node. For instance, in [110], the use of a "chain" structure was proposed to integrate historical knowledge into successive boosting learning.…”
Section: Variations Of the Boosting Learning Algorithmmentioning
confidence: 99%
“…In contrast, we want to use only edges that are discriminative for object detection. It has been an important topic in shape matching and detection to learn discriminative edges and discard unstable ones [14,16]. We use two criteria to select edges: stability to viewpoint and frequency of edge orientations.…”
Section: Selecting Discriminative Edgesmentioning
confidence: 99%
“…The experimental setup is the same as coin detection, except that some parameters are tuned to fit the task. Test images are all normalized to 1654, searching range uses [10,80], and the number of searching radii chooses 15. Other parameters are set using the same way as coin detection.…”
Section: Circular Seal Detection In Document Imagesmentioning
confidence: 99%